Una proposta di legge, frutto della collaborazione della scienza canonistica, sulla sede romana totalmente impedita e la rinuncia del papa (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. La necessità e l’impellenza di una legislazione - 2. Due lacune da colmare - 3. Un primo draft per un appello alla scienza canonistica - 4. L’intervento del legislatore supremo - 5. La sede apostolica totalmente impedita. Impedimento temporaneo - 5.1. Cause fisiche di ordine esterno - 5.2. Cause di ordine personale: inabilità fisica o psichica provvisoria - 6. Inhabilitas totale, certa e perpetua - 7. Brevissima appendice sulla crux teologica e giuridica sottostante - 8. La rinuncia predisposta dal papa per il caso di sua inhabilitas - 9. Il papa che ha rinunciato - 10. Norme conclusive e postfazione sull’impedimento per ‘causa giuridica’.A proposal for a law on the entirely impeded Roman See and the Pope’s resignation as a result of the collaboration of canon law scholarshipIn the first place, the contribution highlights the reasons for the need and urgency of an intervention from the supreme legislator of the Church in order to fill two legal gaps. One of them concerns the regulation of the impeded Apostolic See, both temporarily and - notably - because of a permanent and irreversible impediment of the Roman Pontiff. The second one regards the legal status of a Roman Pontiff who resigned from his office. The potentially problematic matters that would have to be faced and the aspects about which a law should be issued are therefore presented. The ultimate purpose is that of urging and involving the universal canon law scholarship towards an open and constructive discussion in order to develop a carefully examined and considered legislative proposal to be offered to the ecclesiastical authority.